Telecommuting Academics Within an Open Distance Education Environment of South Africa: More Content, Productive, and Healthy? - Tustin, Deon Harold (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2014)
Outside an academic setting, telecommuting has become fairly popular in recent years. However, research on telecommuting practices within a higher education environment is fairly sparse, especially within the higher distance education sphere. Drawing on existing literature on telecommuting and the outcome of a valuation study on the success of an experimental telecommuting programme at the largest distance education institution in South Africa, this article presents discerning findings on telecommuting practices. In fact, the research builds on evolutionary telecommuting assessment methods of the direct or indirect effect (work based) and affective impact (emotional) on multiple stakeholder groups. This holistic approach allowed for comparative analysis between telecommuting and nontelecommuting academics with regard to the impact of telecommuting practices. The research reveals high levels of support for telecommuting practices that are associated with high levels of work productivity and satisfaction, lower levels of emotional and physical fatigue, and reduced work stress, frustration, and overload. The study also reveals higher levels of student satisfaction with academic support from telecommuters than nontelecommuters. Overall, the critique presents insightful findings on telecommuting practices within an academic setting, which clearly signal a potential for a shift in the office culture of higher distance education institutions in the years to come. The study makes a significant contribution to a limited collection of empirical research on telecommuting practices within the higher distance education sector and guides institutions in refining and/or redefining future telecommuting strategies or programmes.